Analytical study of flat and curved trapezoidal cold formed steel sheets by means of the yield line theory. Part 2: Curved sheets with transverse corrugations. (August 2019) - Casariego, P.; Casafont, M.; Ferrer, M.; Marimon, F.
Abstract: The article presents a study of self-supporting arched roofs made from trapezoidal sheets by press-forming a series of transverse corrugations. The study is particularly focused on the effect of these corrugations. To this end, a study has been made of trapezoidal sheets with and without transverse corrugations and the results compared. Three approaches have been considered: Finite Element Method (FEM), experimental tests, and analytical calculations carried out with the Yield Line Theory (YLT). In the first part of the present article, the results of analyses performed with a rather elaborate finite element model are shown, as well as being verified with experimental tests. The FEM results demonstrate that transverse corrugations can have an important effect on the behavior and ultimate strength of the sheets. In the second part, the YLT models developed in the companion article, on the analysis of flat trapezoidal sheets, are adapted to the arched roofs. These analytical models have proved effective in facilitating full understanding of the behavior of curved sheets, as well as predicting, approximately, the loss of strength caused by the transverse corrugations. Highlights: Transverse corrugations provoke a significant loss of load carrying capacity of the sheets. In positive bending, the effect of the corrugation is similar to the effect of a large geometric imperfection. In compression and negative bending, there is a reinitiation of the transverse corrugation forming process. The Yield Line Theory is an effective option to study the effect of transverse corrugations on trapezoidal sheets.